Operaciones lógicas matemáticos y su incidencia en el aprendizaje de los estudiantes de segundo a séptimo año de educación general básica de la Escuela Aurora Estrada y Ayala de Ramírez de la Parroquia Camilo Ponce del cantón Babahoyo, Provincia de Los Ríos - Machacilla Tomalá, Ángel Alejandro (2022)
Logical mathematical operations is a learning process that comes through skills, values and attitudes, where it enables through study the teaching or the student's experience that occurs through stages such as experiential, manipulations, symbolic graphic representations and abstraction. , since children begin to interact with objects, exploring the world around them using all their senses, thereby laying the foundation for what will be important mathematical ideas and concepts in the future, it should be understood that it is one of the essential components for the intellectual development of children, which promotes the structuring and conceptualization of various mathematical knowledge. In this case study, it is possible to explain the concept in a clear and precise way that the subject of mathematics is essential for the intellectual development of children since it helps them to be logical, to reason in an orderly manner and to have their mind prepared to criticism, thought and abstraction